Cover Image. (20th August 2021) - Hu, Kai; Wan, Ji; Luo, Kan; Xu, Yuzhuang; Cheng, Zijing; Tsai, Wei‐Tek
Abstract : The cover image is based on the Original Article Verification Algebra for Multi‐Tenant Applications in VaaS Architecture by Kan Luo et al., https://doi.org/10.1002/stvr.1763 .